Implementation of TPS and Mind Mapping Models in Sociology Learning at SMAN 5 Purworejo - Hirawati, Wahyu; Agustin, Dewien Nabielah (Universitas Tanjungpura, 2025)
This study discusses the strategies used by teachers at SMA Negeri 5 Purworejo to increase students' interest in Sociology subjects because the lesson is often considered boring and uninteresting for students. The purpose of this study was to analyze how the Think Pair Share (TPS) cooperative learning model using the mind mapping method is implemented and how it impacts students' participation and interest in learning. This study uses a qualitative approach and uses data collection techniques through observation, direct observation of the learning process, and interviews to determine students' interest in this learning approach. The results of the study indicate that the Mind Mapping method helps students visualize ideas and understand abstract material, while the Think Pair Share (TPS) model encourages students to work together to solve problems and connect various concepts. The combination of these methods and models creates a more active, collaborative, and enjoyable learning environment. These findings suggest that sociology teachers can utilize the integration of Think Pair Share and Mind Mapping as an effective learning alternative to improve students' learning interest and thinking skills at the secondary school level.